Performance Analysis of OFDMA and SC-FDMA - Muhanned AL-Rawi (Vìsnik Nacìonalʹnogo Tehnìčnogo Unìversitetu Ukraïni Kììvsʹkij Polìtehnìčnij Ìnstitut: Serìâ Radìotehnìka, Radìoaparatobuduvannâ, 2017)
The main challenge in any high-speed digital communication system is how to maximize the data rate with minimizing the bit error rate. Several techniques have been developed to achieve this point. Some of these techniques are orthogonal frequency division multiplexing (OFDM), single-carrier frequency domain equalization (SC-FDE), orthogonal frequency division multiple access (OFDMA), and single-carrier frequency division multiple access (SC-FDMA). These four techniques are described briefly in this paper. Also, the paper measures the performances of OFDMA and SC-FDMA systems over international telecommunication union (ITU) vehicular-A channel using minimum mean square error (MMSE) equalization. Simulation results show that the performances with interleaved mapping outperform that with localized mapping. Also, the performances with quadrature phase shift keying(QPSK) are better than that with 16-ary quadrature  amplitude modulation (16QAM). In addition, the performance of SC-FDMA is better than that of OFDMA, when QPSK is used, but the latter is little bit better than that of SC-FDMA when 16QAM is used